« Das soll Europa sein ? » Jean Cocteau dans l’Europa Almanach de Carl Einstein et Paul Westheim - Klaus H. Kiefer (Recherches Germaniques)
The Europa Almanach, which Carl Einstein et Paul Westheim edited in 1925, was not a political manifesto. The common denominator was art, actually the artistic avant-garde of different European nations. The French contributions were published in the original language, as for example a poem by Jean Cocteau, who also presented six drawings and a witty dialogue (Cocteau interrogates God) and thus was an eminent contributor to the Almanach. Nevertheless, the editors put the portrait of Cocteau by Modigliani in a critical perspective. This editorial strategy can also be seen in the composition of the other texts and images.